News, Reports, Songs
News broadcast on Saddam's visit to Baghdad, an order from the president to his people to put the private electicity generators on every night, Sahhaf says all enemies have been driven out of Saddam's airport; women have died defending Iraq. Report with interviews with Iraqi's on the street, who say that everything is normal and that as long as Saddam is doing fine the Iraqi people are doing fine; readings from local newspapers; report about how Saddam is leading his people to dignity and pride, how the brave Iraqi army defended Baghdad and how Iraq has won again. Report with Sahhaf interview with Al-Jazzera, in which Iraqi Information Minister says: "we killed all the Americans in the airport, and destroyed 7 tanks." Report offering congratulations to every Iraqi who has Saddam as president, for Saddam is winning; replay of reading of local newspapers; report on how all civlians in Baghdad have been turned into soldiers to fight for Iraq and Saddam; report on how Iraq is an example in the world for dignity, pride, and truth; soldiers believe in what they are fighting for; enemy has not yet been able to take even a village.